2007
DOI: 10.1021/ja076488m
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of Histone H4 Aptamers for Recognition Imaging Microscopy

Abstract: Recognition imaging microscopy is an analytical technique used to map the topography and chemical identity of specific protein molecules present in complex biological samples. The technique relies on the use of antibodies tethered to the cantilever tip of an AFM probe to detect cognate antigens deposited onto a mica surface. Despite the power of this technique to resolve single molecules with nanometer-scale spacing, the recognition step remains limited by the availability of suitable quality Supporting Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…monoclonal antibodies) to block the binding 45 of EGFR and its ligands, consequently blocking receptor activation and 46 transduction of post-receptor signals [9,10]. 47 Recent study has shown that EGFR functionality can be dependent 48 on its subcellular location and mis-located EGFR may regulate tumor re- 49 sponse to therapy [11]. Therefore, localization of EGFR on cancer cells is 50 of great importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…monoclonal antibodies) to block the binding 45 of EGFR and its ligands, consequently blocking receptor activation and 46 transduction of post-receptor signals [9,10]. 47 Recent study has shown that EGFR functionality can be dependent 48 on its subcellular location and mis-located EGFR may regulate tumor re- 49 sponse to therapy [11]. Therefore, localization of EGFR on cancer cells is 50 of great importance.…”
mentioning
confidence: 99%
“…Applications of TREC technique in biomedical research is certainly an 231 increasingly demanding task. Up to now, TREC imaging method has 232 been applied to visualize quite a few different biomolecule systems, 233 such as biotin-avidin [44,45], ligand-receptor [46,47], and antibody-234 antigen interactions [20,23]. In this study, we utilized TREC imaging to 235 visualize EGFR molecules on complex cell membrane surface, providing 236 a new example of the applications of this methodology in biomedical re-237 search.…”
mentioning
confidence: 99%
“…Lin et al tested another system of recognition using DNA aptamers, to reduce cross-reactivity and enhance detection (Lin et al, 2007c). These nucleic acid molecules display similar properties to antibody such as their characteristic folding complementary to the structure of their target epitope (Bunka & Stockley, 2006;Colas, 2008).…”
Section: Examples Of Receptor-ligand Analysis In the Context Of Chrommentioning
confidence: 99%
“…13,14 Recently, a number of aptamer-based analytical methods have been developed for protein recognition and detection. [15][16][17][18] However, only a few aptamers have been reported to be potentially useful in histone recognition. 18,19 Recently, Lin et al created an aptamer in vitro by capillary electrophoresis based SELEX (systematic evolution of ligands by exponential enrichment, CE-SELEX) for the histone H4 peptide, and it showed a relatively high affinity towards the histone H4 peptide and could recognize different histone classes in recognition imaging microscopy.…”
mentioning
confidence: 99%